8 people meet, and each person shakes every other person's hand once. how many handshakes occurred?

Answers

Answer 1
Answer: 8x8 = 64

So if every single person handshakes everyone's hand once it would be a total of

64 times
Answer 2
Answer: There was 28 handshakes

Related Questions

the formula for finding the volume of a pyramid is v=bh/3. what formula should I use to find altitude h? a. h=3b/v, b. h=3v/b, c. h=v/3b, or d. h=3bv
If f(x) = (1/8)(8^x), what is f(3)?
Whosever answers first gets marked brainliest!
What is the correct label for the angle?
What is the perimeter of a triangle that has two sides measuring 7 centimeters and a third side measuring 9 centimeters?

I have a square with an area that equals 184 cm^2. How do I find the side and put the answer in simplest radical form?

Answers

We~know,\n\n Area~of~square=l^2\n\nl=√(Area)\n\nl=√(184cm^2)\n\nl=√(2*2*2*23*cm*cm)\n\nl=2√(2*23)~cm\n\nl=2√(46)~cm

Heidi, a jewelry salesperson, earns a commission of $55 every time she sells a diamond ring. How many rings does she have to sell to earn $605? Choose the equation that correctly calculates the amount.a. $605 – $55 = w
b. $55 w = $605
c. $55 × w = $605
d. $55 – w = $605 – w

Answers

b and c are correct
If we use w for the number of rings she sells we might ask:
$55  times how many rings she sells (w) gets her $605 in commissions.
$55 x w = $605
or you may skip the times sign (x) because when number appears next to a variable (such as w) they are connected by multiplication
so
$55w = $605 is the same thing as $55 x w = $605.

sorry for the really late answer. but its (C)

The measure of an angle is 4y. find the measure of its complement.

Answers

180 should be the answer

What is the product? assume x>0 (√3x + √5) (√15x +2√30

Answers

The first step for solving this expression is to multiply the parenthesis.
√(45) x^(2) +  2√(90) x +  √(75)x + 2√(150)
Simplify the first radical.
3√(5) x^(2) + 2√(90) x + √(75)x + 2√(150)
Simplify the second radical.
3√(5) x^(2) + 2X3√(10) x + √(75)x + 2√(150)
Simplify the third radical.
3√(5) x^(2) + 2X3√(10) x + 5√(3)x + 2√(150)
Simplify the final radical.
3√(5) x^(2) + 2X3√(10) x + 5√(3)x + 10√(6)
Lastly,, calculate the product of 2 × 3√(10)x to get your final answer.
3√(5) x^(2) + 6√(10) x + 5√(3)x + 10√(6)
Let me know if you have any further questions.
:)

Answer: B: 3x√5+6√10x+5√3x+10√6x

Step-by-step explanation:

What is the difference between rational exponents and integer exponents? Select one: a. There is no difference. b. Rational exponents are whole numbers and integer exponents are fractional exponents. c. Rational exponents are fractional exponents and integer exponents are whole numbers. d. Integer exponents are always positive while rational exponents are negative and positive.

Answers

The correct answer is Option (C) Rational exponents are fractional exponents and integer exponents are whole numbers

What is Rational Exponents?

  • Rational exponents aresimplya fraction representing an exponent that is rewritten as a radical expression.

What is Integer Exponents?

  • The exponents containing an integer is Known as Integer Exponents.

What is difference between Rational exponents and integer exponents?

  • Integer means Whole numbers whereas Rational means fraction with whole numbers
  • Hence Rational exponents and integerexponents both contains whole number but rational exponents contains fraction with whole numbers

Hence the correct option is (C)  Rational exponents are fractional exponents and integer exponents are whole numbers

Learn more about Rational exponents here

brainly.com/question/2004951

#SPJ2

Answer:

The answer is A

Step-by-step explanation:

What is the value of x?



x =

Answers

The formula we need is this one: EC(EC+CD)=EB(EB+BA).  Filling in accordingly, we have x+4(x+4+1)=x+1(x+1+11).  Simplifying that we get (x+4)(x+5)=(x+1)(x+12).  We will FOIL both sides to get x^2+9x+20=x^2+13x+12.  Combining like terms gives us this simplification: 0=4x-8.  If we factor out the common 4, we have 0 = 4(x-2).  By the Zero Product Property, eitheer 4=0 or x-2=0.  Well obviously, 4 does not equal zero, so x-2 = 0, and x = 2.